Association of physical activity with arterial stiffness among Black adults. (February 2022) - Islam, Shabatun J; Beydoun, Nour; Mehta, Anurag; Kim, Jeong Hwan; Ko, Yi-An; Jin, Qingchun; Baltrus, Peter; Topel, Matthew L; Liu, Chang; Mujahid, Mahasin S; Vaccarino, Viola; Sims, Mario; et al.
Arterial stiffness is a precursor for the development of hypertension and premature cardiovascular disease (CVD). Physical activity has been associated with lower arterial stiffness among largely White populations, but the types of activity required and whether these findings apply to Black adults remain unknown. We examined whether physical activity levels were associated with arterial stiffness among Black adults in two independent cohorts. In the Morehouse-Emory Cardiovascular (MECA) Center for Health Equity, 378 Black adults (age 52.8 ± 10.3, 39.7% male) without known CVD living in Atlanta, GA were recruited. Arterial stiffness was measured as pulse wave velocity (PWV). Total and domain-specific physical activity were assessed by self-report. Multiple linear regression models were used to investigate differences across physical activity levels after adjusting for age, sex, CVD risk factors, and socioeconomic status. Findings were validated in an independent cohort of Black adults ( n = 55, age 50.4 ± 9.2, 23.6% male). After adjustment for covariates, lower arterial stiffness was associated with higher self-reported levels of sport/exercise (6.92 ± 1.13 vs 7.75 ± 1.14, p < 0.001, highest vs lowest quartile) and home/life activities (7.34 ± 1.24 vs 7.73 ± 1.07, p = 0.04, highest vs lowest quartile), but not work, active living, or the overall physical activity scores. These findings were replicated in the independent cohort where higher levels of sport/exercise remained associated with lower arterial stiffness (6.66 ± 0.57 vs 8.21 ± 0.66, p < 0.001, highest vs lowest quartile). Higher levels of sport/exercise and home/life-related physical activities (in comparison to occupational physical activity) are associated with lower arterial stiffness in Black adults.